Stacking three late blight resistance genes from wild species directly into African highland potato varieties confers complete field resistance to local blight races - Ghislain, M.; Byarugaba, A.A.; Magembe, E.; Njoroge, A.W.; Rivera, C.; Roman, M.L.; Tovar, J.C.; Gamboa, S.; Forbes, G.; Kreuze, Jan F.; Barekye, A.; Kiggundu, A. (Wiley, 2018)
Considered responsible for one million deaths in Ireland and widespread famine in the European continent during the 1840s, late blight, caused by Phytophthora infestans, remains the most devastating disease of potato (Solanum tuberosum L.) with about 15%–30% annual yield loss in sub‐Saharan Africa, affecting mainly smallholder farmers. We show here that the transfer of three resistance (R) genes from wild relatives [RB, Rpi‐blb2 from Solanum bulbocastanum and Rpi‐vnt1.1 from S. venturii] into potato provided complete resistance in the field over several seasons. We observed that the stacking of the three R genes produced a high frequency of transgenic events with resistance to late blight. In the field, 13 resistant transgenic events with the 3R‐gene stack from the potato varieties ‘Desiree’ and ‘Victoria’ grew normally without showing pathogen damage and without any fungicide spray, whereas their non‐transgenic equivalent varieties were rapidly killed. Characteristics of the local pathogen population suggest that the resistance to late blight may be long‐lasting because it has low diversity, and essentially consists of the single lineage, 2_A1, which expresses the cognate avirulence effector genes. Yields of two transgenic events from ‘Desiree’ and ‘Victoria’ grown without fungicide to reflect small‐scale farm holders were estimated to be 29 and 45 t/ha respectively. This represents a three to four‐fold increase over the national average. Thus, these late blight resistant potato varieties, which are the farmers’ preferred varieties, could be rapidly adopted and bring significant income to smallholder farmers in sub‐Saharan Africa